SYNTHESIS OF INOSITOL IN MICE - Woolley, D. W. (The Rockefeller University Press, 1942)
It has been shown that mice are able to synthesize inositol. This synthesis was not observed when pantothenic acid was absent from the diet. Cultures from the intestinal tract of animals which exhibited spontaneous cure of alopecia yielded microorganisms which synthesized much more inositol than did organisms isolated in the same fashion from the tracts of mice that had become hairless. Some observations on the distribution of free and combined inositol have been made and it has been shown that several biological materials contain combined inositol. It has been found that deficiency of inositol can develop even when inositol is present in the diet if pantothenic acid is omitted.